2019
DOI: 10.1177/0956797619864598
|View full text |Cite
|
Sign up to set email alerts
|

Hide or Seek? Physiological Responses Reflect Both the Decision and the Attempt to Conceal Information

Abstract: The process of information concealment is more relevant than ever in this day and age. Using a modified concealed-information test (CIT), we aimed to unmask this process by investigating both the decision and the attempt to conceal information in 38 students. The attempt to conceal (vs. reveal) information induced a differential physiological response pattern within subjects—whereas skin conductance increased in both conditions, respiration and heart rate were suppressed only in the conceal condition—confirmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 43 publications
3
25
1
1
Order By: Relevance
“…First, although no significant differences were found when comparing the misinformation and control conditions, the SCR CIT effect was only significant in the misinfo‐all condition, while the RLL CIT effect was only significant in the misinfo‐narr condition. Whether this is a chance finding, or possibly caused by different underlying mechanisms driving the various physiological measures (i.e., [31–33]), remains an open question for future research. Importantly however, it implies that our conclusion should be made with great caution and the role of misleading information in the CIT requires additional studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, although no significant differences were found when comparing the misinformation and control conditions, the SCR CIT effect was only significant in the misinfo‐all condition, while the RLL CIT effect was only significant in the misinfo‐narr condition. Whether this is a chance finding, or possibly caused by different underlying mechanisms driving the various physiological measures (i.e., [31–33]), remains an open question for future research. Importantly however, it implies that our conclusion should be made with great caution and the role of misleading information in the CIT requires additional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, exposure to misinformation in the context of the crime potentially adds significance to the misinformation items, which thus elicit enhanced responses compared to control items, making it harder to detect relevant hidden knowledge. This explanation especially holds for the SCR measure which has been shown to reflect an orientation process [31–33].…”
Section: Introductionmentioning
confidence: 99%
“…Because of individual differences in physiological responsivity, within‐subject standard Z‐scores were calculated separately for SCR and HR (the target item was excluded from the standardization, Klein Selle et al, 2019). For SCR and HR measures, those responses were removed if the Z‐scores were larger than 5 or smaller than −5.…”
Section: Methodsmentioning
confidence: 99%
“…In the physiological‐measure‐based CIT, a typical response pattern for a person who recognizes crime‐related information includes larger SCRs, a shorter RLL, and a decelerated HR, which is also called the CIT effect. Studies have recently suggested that these physiological responses are driven by different mechanisms and could be explained by the response fractionation model (Klein Selle et al, 2019). The increased SCR reflects an orienting response, whereas RLL and HR reflect attempts to inhibit arousal (AI; Klein Selle et al, 2016; Verschuere et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Guilty suspects, on the contrary, show an increased skin conductance response (SCR), a deceleration of heart rate (HR) and respiratory suppression (usually defined as shortening of the total respiration line length; RLL) upon recognition of critical items. This pattern has been explained by an increased orienting response toward the recognized significant item and the deliberate attempt to inhibit the physiological arousal experienced when confronted with critical crime details (klein Selle et al 2016(klein Selle et al , 2017(klein Selle et al , 2019.…”
Section: Introductionmentioning
confidence: 99%